Electrocatalytic activity of nanohybrids based on carbon nanomaterials and MFe2O4 (M= Co, Mn) towards the reduction of hydrogen peroxide - Gutierrez, Fabiana A. (2018)
We report the advantages of hybrid nanomaterials prepared with electrogenerated ferrites (MFe2O4; M: Co, Mn) and multi-walled carbon nanotubes (MWCNTs) or thermally reduced graphene oxide (TRGO) on the electro-reduction of hydrogen peroxide. Glassy carbon electrodes (GCE) modified with these hybrid nanomaterials dispersed in Nafion/isopropanol demonstrated a clear synergism on the catalytic reduction of reduction of hydrogen peroxide at pH 13.00. The intimate interaction between MFe2O4 and carbon nanomaterials allowed a better electronic transfer and a facilitated regeneration of M2+ at the carbon nanomaterials, reducing the charge transfer resistances for hydrogen peroxide reduction and increasing the sensitivities of the amperometric response.